Fatigue performance of orthogonally reinforced concrete slabs: Experimental investigation. (1st August 2018) - Spathelf, C.A.; Vogel, T.
Highlights: The fatigue performance of concrete slabs was investigated in large scale tests. Measurements of reinforcement strains indicate fatigue failure of individual bars. Slabs exhibit a significant remaining fatigue life after failure of first bar. Fatigue strength unaffected by deviation between moment and reinforcement direction. Abstract: The fatigue performance of reinforced concrete slabs was investigated under clearly defined bending conditions with large scale tests. Two series of four tests exhibiting orthogonal reinforcement layouts at different orientations were subjected to constant force-amplitude cyclic loading. The reinforcement direction in the reference series of tests coincided with the direction of principal moment. In the second series of tests, a deviation of 45° between the principal moment and reinforcement direction was introduced. The effect of inclined reinforcing bars with respect to the principal moment direction on the fatigue strength of structural concrete slabs is described. Direct measurement of reinforcing steel strains enabled a characterisation of the redistribution of internal forces within the cross-section after failure of individual bars until global failure of the slab.